2009
DOI: 10.1177/1721727x0900700307
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Deoxyribonuclease Treatment in Hospital Management of Infants with Moderate-Severe Bronchiolitis

Abstract: Bronchiolitis is the main cause of respiratory insufficiency in infants, characterized by acute inflammation, edema, necrosis of epithelial cells and increased mucus production. Mucus is mainly purulent and consequently rich in DNA, as derived from nuclei of degenerating neutrophils and epithelial debris. The treatment is mainly supportive; bronchodilators and systemic steroids are often used but do not reduce the length of hospital stay. The aim of our study is to evaluate the efficacy of recombinant human DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Addition of DNA to mucus increases viscosity in vitro . In this context, some studies have assessed the effects of nebulized recombinant DNase in children with RSV–LRTD to reduce mucus viscosity and decrease airway obstruction . One clinical trial showed strong radiological improvement and one case‐series in mechanically ventilated infants with severe RSV–LRTD showed clinical and radiological improvement .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of DNA to mucus increases viscosity in vitro . In this context, some studies have assessed the effects of nebulized recombinant DNase in children with RSV–LRTD to reduce mucus viscosity and decrease airway obstruction . One clinical trial showed strong radiological improvement and one case‐series in mechanically ventilated infants with severe RSV–LRTD showed clinical and radiological improvement .…”
Section: Discussionmentioning
confidence: 99%
“…One clinical trial showed strong radiological improvement [10] and one case-series in mechanically ventilated infants with severe RSV-LRTD showed clinical and radiological improvement [46]. Unfortunately, in two more recent randomized, placebo-controlled trials, DNase treatment did not reduce the duration of admission or oxygen need of hospitalized infants with RSV-LRTD [47,48]. However, it is possible that this negative result is related to the relatively mild RSV disease in the populations studied, or to the difficulty for the agent to reach the more distal and heterogeneous distributed airway plugs.…”
Section: Nets Are Formed In Plugs Obstructing the Airways In Brsv-lrtmentioning
confidence: 99%
“…The therapy for bronchiolitis is mainly supportive [5], with supplemental oxygen, nasal washing, and intravenous (IV) fluids. Clinical trials, testing β 2-agonists [6,7], glucocorticoids [8], epinephrine [9], recombinant human DNase [10,11], and hypertonic saline [12] in bronchiolitis report highly controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…I.e); 6) lymphoid interstitial pneumonia (LIP), characterized by lymphoid and plasma cellular infiltration of alveolar septa and peribronchiolar and periarteriolar interstitium; 7) giant cell interstitial pneumonia (GIP) is less common than the others and has a lymphocytic and plasmacytic infiltrate with giant cells in alveoli in a great phagocytic activity and they can be, in fact, defined as cannibal. These types, more than autonomous entities, are considered different evolutive phases of an interstitial reaction to equal stimuli or expressions of a lung change as a reaction to damaging agents of different kinds (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Another classification links interstitial lung diseases with more or less homogeneous aetiological factors, marking two main groups: a) interstitial lung diseases of known aetiology (infective agents, organic dusts, inorganic dusts, chemical dusts, gases, fumes, exhalations, aerosols, poisons, ionizing radiations, medicines); b) interstitial lung diseases of unknown aetiology (familiar and sporadic idiopathic lung fibrosis, collagen-vascular diseases, sarcoidosis, histiocytosis X, Goodpasture syndrome, eosinophilic pneumonia, lymphangioleiomyomatosis, hereditary diseases, infiltrative lymphocytic diseases, lung vasculitis, idiopathic lung haemosiderosis, alveolar proteinosis, lower airways diseases, Weber-Christian disease, hypereosinophilic syndromes, lung veinocclusive disease, lung carcinomatous lymphangitis, haemodynamic changes, chronic kidney failure, gastro-esophageal reflux with chronic aspiration, bowel diseases, liver diseases) and a newer one considers: I) idiopathic interstitial pneumonias 2) environmental and occupational diseases 3) multisystem diseases 4) rare lung diseases.…”
Section: Classificationmentioning
confidence: 99%